SELECTION OF EQUIPMENTFOR PROCESSING ANCIENT GRAINS - V. Petrov; A. Aleksashin; S. Pozner (Zernovì Produkti ì Kombìkorma)
Recently, there has been a sharp increase in interest in the consumption of ancient grain crops (spelt, einkorn, emmer). In this connection, the sown areas for these crops are increasing, and the main volume of grown cereals is not for animal consumption, but for human consumption. Such a shift in consumption leads to increased requirements for the quality of grain and its processing products. Taking into account the increase in processing volumes, it is necessary to use serial high-performance equipment, which, unfortunately, does not satisfy grain processors due to the peculiarities of the structure of the grain and ears of these grain crops, which affects its efficiency. The paper considers various designs of huskers that are trying to be used in husking spelt and other grain crops. Their technological schemes have been built and analyzed from the point of view of the efficiency of spelt processing. This allowed us to group different designs of huskers and summarize their technological capabilities. Technological schemes with different peeling machines (peeling machine with abrasive discs, with rubber shafts, centrifugal action, impact peelers using a vibropneumatic table and friction separator) were analyzed, which have their own characteristics in separating peeled grain from unpeeled. A general abbreviated technological scheme for cleaning and peeling spelt grain was considered. Its variations in terms of practical application were indicated. A peeler design with an improved scheme for installing a sieve basket was developed. When introducing the newly created equipment at the enterprises of the industry, it was found that the use of an impact-peeling machine allows to improve economic performance: increase labor productivity by 1.375 times, reduce specific electricity consumption by 3.3 kW, obtain a profit of 290,153 UAH, recoup capital investments in 2.12 years, which is economically feasible. The calculations performed indicate the economic feasibility and economic efficiency of improving the impact-peeling machine.